Techniques and approaches for revascularisation of left heart coronary diseases. (2nd August 2020) - Maskell, Perry; Oo, Shwe; Muir, Andrew D; Fan, Ka Siu; Harky, Amer
Abstract : Coronary artery disease and its associated clinical sequelae are a significant medical burden to clinicians and patients. Severe coronary artery disease presenting in the context of acute myocardial ischaemia, or stable plaques causing chronic symptoms despite best conservative and pharmacological intervention, are often amenable to further intervention such as coronary artery bypass grafting. This procedure has been extensively compared to newer and less invasive techniques, such as percutaneous coronary intervention, and other minimally invasive procedures such as robotic or endoscopic techniques. This review summarises the current evidence on revascularisation of the left coronary artery system, with particular emphasis on key clinical endpoints of mortality, myocardial infarction, stroke and repeat revascularisation.